2009
DOI: 10.1097/01.aoa.0000362070.37398.1c
|View full text |Cite
|
Sign up to set email alerts
|

Maternal Gestational Weight Gain and Offspring Weight in Adolescence

Abstract: Objective-To study associations of maternal gestational weight gain with offspring weight status in adolescence.Methods-We surveyed 11,994 adolescents aged 9-14 enrolled in the Growing Up Today Study cohort and their mothers, members of the Nurses' Health Study II. We used multivariable linear and logistic regression to study associations of gestational weight gain with offspring adiposity.Results-Mean (SD) gestational weight gain was 31.5 (11.2) pounds and offspring BMI z-score (BMI standardized for age and s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

14
132
1
12

Year Published

2009
2009
2018
2018

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 107 publications
(159 citation statements)
references
References 18 publications
14
132
1
12
Order By: Relevance
“…26 GWG is positively associated with birth weight even when stratifying on factors such as maternal BMI, age, parity and educational level. 27 In accordance with others, [11][12][13][14][15][16] our data suggest that birth weight is not a predominant mediator of the effect of GWG on offspring BMI. Instead, these intrauterine effects could be related to permanent modulation of appetite control, neuro-endocrine pathways influencing adipose tissue development and function or Gestational weight gain and offspring obesity L Schack-Nielsen et al energy metabolism causing development of obesity in later life.…”
Section: Discussionsupporting
confidence: 87%
See 2 more Smart Citations
“…26 GWG is positively associated with birth weight even when stratifying on factors such as maternal BMI, age, parity and educational level. 27 In accordance with others, [11][12][13][14][15][16] our data suggest that birth weight is not a predominant mediator of the effect of GWG on offspring BMI. Instead, these intrauterine effects could be related to permanent modulation of appetite control, neuro-endocrine pathways influencing adipose tissue development and function or Gestational weight gain and offspring obesity L Schack-Nielsen et al energy metabolism causing development of obesity in later life.…”
Section: Discussionsupporting
confidence: 87%
“…16 In three of these studies, [11][12][13] the prevalence of maternal and childhood overweight was higher than in our study. This consistency is particularly important because our cohort had an overrepresentation of mothers with previous or current pregnancy complications as well as single mothers, whereas the study populations of the other studies were characterized as socially advantaged, 11,15 nationally representative 12 or multiethnic. 14 In contrast, studies with other primary focuses have reported no effect of GWG on offspring BMI in childhood 25 or young adulthood.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The observation that excessive GWG in the third trimester is associated with a risk for childhood overweight while its avoidance is protective matches the available evidence for the association between excessive total GWG and childhood overweight (8)(9)(10)(11)(12)(13) and reflects the high positive predictive value of excessive third trimester for total excessive GWG (81.4%, 85.0%, 90.0% and 96.1% for obese, overweight, normal weight, and underweight mothers, respectively) demonstrated recently (16). Importantly, the association could not be explained by maternal BMI.…”
Section: Discussionsupporting
confidence: 68%
“…Effective early preventive strategies are therefore urgently needed. A growing body of longitudinal research indicates that childhood overweight (8)(9)(10)(11)(12)(13) and higher proportions of body fat in children (8,14) are associated with excessive gestational weight gain (GWG) via mechanisms referred to as foetal programming (8)(9)(10)(11)(12)(13).…”
Section: Introductionmentioning
confidence: 99%